The Relationship Between Inherent And Acquired Characteristics Of Human Development With Marital Adjustment - YILDIRIM, MELİS SERAY ÖZDEN (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
In the study, the dyadic adjustments in marital relationships of young adults between ages 20-45, their temperament properties that are supposed to be brought natively and the relationships between the attitudes they perceived from their parents which are known as to be gained afterwards, separation-individuation and the adaptation of resilience have been analysed. The Personal Information Form, The Dyadic Adjustment Scale, Five Factor Personality Inventory (Short Form), The Resilience Scale, The Scale of Separation-Individuation and Perceived Parental Attitudes - Mother and Father Forms have been carried out on the sampling group of 135 couples living in Istanbul. As a result of the research, there is positively significant relation between extraversion, openness to experience and marital adjustment in both men and women. Neuroticism and marital adjustment is related negatively for both genders. The agreeableness is related positively with marital adjustment only for men. As the resilience of both women and men increases, the marital adjustment also increases. The marital adjustment level decreases when both women and men fail to practice separation-individuation successfully. The marital adjustment levels of the men gets higher when they perceive that there autonomy is supported by their mothers. The marital adjustment levels of the men decreases when they perceive that they are kept under control psychologically by their mothers. Similarly, the marital adjustment levels of the men decreases when they perceive that they are kept under control psychologically by their fathers. The marital adjustment levels of the men increases more when they perceive that their autonomy is supported by their fathers and their fathers are more sensitive, tender and concerned. It is found out that there is no relation between the parental attitudes the women from the sampling group perceived from their mothers and the marital adjustment. Also the marital adjustment levels of the women increases more when they perceive that their fathers are more sensitive, tender and concerned and their autonomy is supported by their fathers. The marital adjustment levels of the women decreases who perceive that their fathers have a manipulative and compulsive control. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Marital Adjustment; Temperament; The Power of Recovery; Seperation-Individuation; Perceived Parent Attitudes